2017
DOI: 10.4313/teem.2017.18.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Conventional and Microwave Sintering of Large Strain Bi-Based Perovskite Ceramics

Abstract: A comparative study of microwave and conventional sintering of lead-free Bi 1/2 (Na 0.82 K 0.18 ) 1/2 TiO 3 -BaZrO 3 -CuO ceramics is presented. It was found that microwave sintering (MWS) can be successfully applied to the fabrication of large strain Bi-perovskite with electric field-induced strains comparable to those obtained with conventional sintering (CFS). Although MWS resulted in smaller grained microstructures than CFS, the ferroelectric properties were stronger in MWS-derived specimens than in the CF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…It is found that the grain size tends to be smaller with the increase of BF content, that is, it decreases from 56.72 μm to 18.50 μm as a function of BF, suggesting that the excess BF can inhibit the grain growth. Compared with CS samples, the grain size is smaller in MWS ceramics (see Figure 4 i), proving that the MWS method can also hinder the growth of grain in ceramics; such a phenomenon has been obtained elsewhere [ 22 , 23 , 24 ]. Significantly, the grain size of MWS BTS-BCT- x BF ceramics is close to CS with the increase of doping concentration starting from 0.008, while still a little smaller than the grain size of CS.…”
Section: Resultsmentioning
confidence: 57%
“…It is found that the grain size tends to be smaller with the increase of BF content, that is, it decreases from 56.72 μm to 18.50 μm as a function of BF, suggesting that the excess BF can inhibit the grain growth. Compared with CS samples, the grain size is smaller in MWS ceramics (see Figure 4 i), proving that the MWS method can also hinder the growth of grain in ceramics; such a phenomenon has been obtained elsewhere [ 22 , 23 , 24 ]. Significantly, the grain size of MWS BTS-BCT- x BF ceramics is close to CS with the increase of doping concentration starting from 0.008, while still a little smaller than the grain size of CS.…”
Section: Resultsmentioning
confidence: 57%